Can we say no? : the challenge of rationing health care - Aaron, Henry J. (Brookings Institution Press, 2005)
"Examines the use of rationing as a means to curb health care spending, using the experience of Great Britain to highlight the promises and pitfalls of this approach"--Provided by publisher
Keywords: Health care rationing -- Great Britain.; Health care rationing -- United States.; Medical care, Cost of -- Great Britain.; Medical care, Cost of -- United States.; Health Care Rationing; Health Expenditures; United Kingdom; United States; Soins médicaux -- Rationnement -- Grande-Bretagne.; Soins médicaux -- Rationnement -- États-Unis.; Soins médicaux -- Coût -- Grande-Bretagne.; Soins médicaux -- Coût -- États-Unis.; MEDICAL -- Health Risk Assessment.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; Health care rationing; Medical care, Cost of; Great Britain; Gezondheidszorg.; Financiering.